THE EFFECT OF BENSON'S RELAXATION TECHNIQUE ON PATTERNS SLEEP OF DIABETES MELLITUS PATIENTS - Fira Devi Ernija; Rina Adrianis Telaumbanua; Putri Mawaddah; Elis Anggeria (Universitas Kusuma Husada Surakarta, 2025)
Health problems such as metabolic disorders, which cause osmotic diuresis and dehydration, are experienced by diabetes mellitus patients, with manifestations of nocturia, as well as stress and anxiety disorders that result in reduced sleep quality. This can influence the management of diabetes mellitus treatment to be less than optimal. The aim of this study was to determine the effect of Benson relaxation on sleep patterns in diabetes mellitus patients. The type of research used is a quasi experiment with a pre and post test design without control group, which means that this research design does not have a comparison group. The population in this study were 74 patients diagnosed with diabetes mellitus which resulted in sleep pattern disturbances at RSU Royal Prima Medan during the last month. The sample in this study was 62 people using purposive sampling. Data collection in research uses instruments in the form of observation sheets. Research data analysis was univariate and bivariate analysis using the Wilcoxon rank test. The results of the study explaining the sleep patterns of diabetes mellitus patients before using the Benson relaxation technique showed that the majority of respondents' sleep patterns were poor, 43 people (69.4%), the sleep patterns of diabetes mellitus patients after using the Benson relaxation technique, it was found that the majority of respondents' sleep patterns were good, 32 people. (51.6%), and there was an influence of the Benson relaxation technique on improving sleep patterns in diabetes mellitus patients (p= 0.048). The conclusion of this research is that there is an influence of the Benson relaxation technique on improving the sleep patterns of diabetes mellitus patients at RSU Royal Prima Medan.